Functional sympatholysis and blood flow: regulatory changes with duty cycle, sodium intake, and dietary nitrate supplementation - Caldwell, Jacob Troy (Kansas State University, 2018)
During exercise, muscle blood flow (Q ̇m) increases to match metabolic demand of the active skeletal muscle. In order for this matching to take place, ‘competition’ between local vasodilating metabolites and sympathetically mediated vasoconstriction, termed “functional sympatholysis,” must take place. A key feature of functional sympatholysis is that it is driven largely by metabolic rate (i.e., a higher work rates lead to greater sympatholysis), but may also be largely dependent on nitric oxide bioavailability and oxidative stress in certain disease states (e.g., hypertension). Thus, evaluation of these factors may provide valuable insight into the vascular control mechanisms during exercise in both health and disease. Therefore, the purpose of this dissertation was to 1) determine the role metabolic rate and blood flow on mediating functional sympatholysis, 2) determine the role of nitric oxide bioavailability on functional sympatholysis with high salt intake, a risk factor for primary hypertension, and 3) determine the effect of increases in nitric oxide bioavailability on functional sympatholysis in primary hypertension patients. In the first investigation (Chapter 1), we increased the relaxation phase of the contraction-relaxation cycle to increase active skeletal muscle blood flow (Q ̇m) and see if this would impact vasoconstriction of the active skeletal muscle. We showed that a decreased relaxation time led to greater functional sympatholysis. Interestingly, despite a lower metabolic rate (15% and 20% MVC), we showed that there was no difference in vasoconstriction between the increased relaxation times. These results may show that increases in Q ̇m play a role in functional sympatholysis when mechanical compression is minimized. In the second investigation (Chapter 2), we sought to determine if high dietary sodium (HS) intake would impact functional sympatholysis. We showed that HS intake (15g/day for 7 days) did not impact functional sympatholysis during exercise. Importantly, we show a significant increase in mean arterial pressure (i.e., pressor response) during handgrip exercise. These findings show the deleterious changes in blood pressure, but further work is needed to pinpoint specific mechanisms causing the responses. In the final investigation (Chapter 3), we used an acute nitrate rich (NR) supplement to improve NO bioavailability in hypertensive post-menopausal women (PMW), and observe the impact on functional sympatholysis. We provide novel evidence that functional sympatholysis is improved (~50%) with a NR supplement. The finding that a NR supplement can attenuate vasoconstriction in hypertensive PMW sheds light on the complexities of hypertension, functional sympatholysis and NO bioavailability. The current results indicate that the ‘competition’ between vasodilating metabolites and sympathetically mediated vasoconstriction can be independently modified in health and disease. In individuals with impairment to local vasodilation (e.g., hypertension), the ability to increase functional sympatholysis and muscle blood flow may lead to improvements in cardiovascular health. Taken together, the present results suggest that modifying duty cycle, sodium intake, and NO bioavailability are important factors to be considered with regard to overall cardiovascular health.
Keywords: Blood flow; Handgrip Exercise; Lower body negative pressure